Particle velocity and circulation rate in liquid spouted beds - Kim, S.J.; Cho, S.Y. (Springer-Verlag, 1991)
In this work, the particle velocity and circulation rate in water spouted beds of small glass particles are experimentally studied. The pathline, velocity and residence time of particles 0.53 to 1.40 mm in diameters were measured in the annulus of half-cylindrical columns 40, 60 and 90 mm in diameters. The particle velocity in the annulus and circulation rate increase practically linearly with fluid flowrate. As the column diameter was increased, the average particle velocity in the annulus was decreased, but the particle circulation rate was increased. ？ 1991 Korean Institute of Chemical Engineering.